PKM PENINGKATAN PEMAHAMAN KONSEP MOTIVASI BELAJAR SISWA DENGAN METODE PERMAINAN PADA MATERI PERKALIAN BILANGAN DI KELAS II DI MI NURUL FALAH DESA CIBENDUNG TAKTAKAN - Sarah Caesarani; Resi Wulandari (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
This Community Service is motivated by the low understanding of students' mathematical concepts because the learning process does not optimize the use of media for understanding the concepts of learning material and does not provide students with active participation in the learning process. This Community Service is a Community Service that aims to improve students' understanding of mathematical concepts. The subjects of Community Service are grade II students of MI Nurul Falah totaling 15 students, consisting of 14 male students and 16 female students. Data collection techniques used in the form of tests and scores. The test includes items and the test does not include observations, interviews, and documents. The data analysis techniques used are qualitative descriptive analysis to analyze the results observed in each cycle, and quantitative descriptive analysis to analyze the results of the final assessment of students' understanding of mathematical concepts in each cycle. This Community Service takes place in three cycles. The results of Community Service show that the use of picture bags can improve the understanding of mathematical concepts of MI Nurul Falah grade II students. This is shown by the increase in the level of completeness of student learning from cycle I to cycle III. In cycle I the level of student achievement reached 40%, cycle II increased to 66.67 n cycle III increased to 80%. The criteria for the completeness of this Community Service is 75%, so it can be concluded that the use of picture bags can improve the understanding of mathematical concepts